The role of strategic Agility in organizational excellence In Ministry of Construction, Housing, Municipalities and Public Works - العامري فراس محمد; حسين وجدان ناصر (Journal of Economics and Administrative Sciences, 2019)
The aim of this research is to identify the role of strategic agility achieving organizational excellence in one of the formations of the Ministry of Municipalities (Dhi Qar Sewage Directorate), as important service organizations that have a key role in serving and developing the society which faced many administrative challenges and issues and as a result of the changes in the environment is continuing and accelerating, so the adoption of modern administrative concepts such as strategic Agility and knowledge of their role in achieving organizational excellence can help them in facing these changes and achieve what they aspire to. In order to achieve research objectives, two main hypotheses have been formulated. The first hypothesis tries to find the correlation between the two variables: Strategic Agility and organizational excellence, while the second hypothesis tries to prove the effect of the first variable in the second sample of this research was selected in a random stratified sample consisting of (56) staff members who occupy senior administrative and supervisory positions in the organization. The questionnaire was adopted as a tool for obtaining. The research reached a set of conclusions, the most important of which is that the level of Strategic Agility and organizational excellence in the organization investigated was high for both variables, And that there are a strong correlation and impact of strategic Agility with organizational excellence.